KONSEP DASAR KOMUNIKASI PENDIDIKAN - Karman; Anisa Nurul Ikhsan; Ananda Salma Khoerunnisa; Annisa Fitriyani; Deden Sofwan Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Communication is the process or action of conveying a message from the sender to the recipient through a medium that usually experiences interference. In the world of education, communication has a very important role because it is a process of teaching and learning activities for educators which will build students' understanding of the material being taught. Through communication as a source of conveying information is learning material to recipients, namely students, using symbols both spoken, written and non-verbal language. On the other hand, students will convey various messages in response to the teaching staff so that two-way communication occurs in order to increase the success of communication to achieve learning goals, namely changes in behavior in students. So the goals of education will also be more meaningful if there is intensive communication between teachers and students. Because with intensive communication, teachers can find out the psychological condition of students and the level of students' emotional development. Apart from that, teachers also know accurately the level of difficulty experienced by students in the learning process.